Designing a Web-Based Yakuza Music Studio Booking System - Hosana, Hosana Kristiani Aritonang; Perangin-Angin, Johanes Terang Kita; Hendrik, Jackri (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
Service digitization has become a primary need to improve efficiency and quality, including in the entertainment industry such as music studios. Yakuza Music Studio currently uses a manual booking system that is prone to recording errors and scheduling conflicts. To address these issues, a web-based music studio room booking system was designed using the Rapid Application Development (RAD) method. The RAD method was chosen because of its ability to accelerate the system development process through prototype iterations that directly involve users. This system is designed with key features such as room booking, payment confirmation, promotions, a studio gallery, schedule management, musical instrument inventory, and an admin dashboard for data management. Test results show that the developed system is able to increase the speed and accuracy of the booking process and provide convenience for users and admins. By implementing the RAD method, system development becomes more flexible and responsive to user needs.